Efektivitas Pendistribusian Dana Zakat pada Amil Zakat Nasional BAZNAZ Provinsi Sumatera Utara: Effectiveness of Distribution of Zakat Funds to the National Zakat Amil BAZNAZ, North Sumatra Province - Nurfuadi, Wika; Yenni Samri Juliati Nasution (Litera Academica Publishing, 2025)
This study aims to analyze the effectiveness of the distribution of zakat funds carried out by BAZNAS North Sumatra Province, and identify the impact of zakat distribution on the welfare of mustahik, North Sumatra Province which has a significant Muslim population and large zakat potential. The method used is qualitative with descriptive analysis with literature study to collect related data. The results show that BAZNAS North Sumatra Province has implemented various economic empowerment programs, the level of distribution of zakat funds by BAZNAS North Sumatra Province shows that it has been distributed effectively as shown from some literature that the author found, and has made a positive contribution in increasing the income and welfare of mustahik for a while, but it has not been effective in improving the welfare of mustahik in the long term.